Enhancing the role of university towards sustainable development of the nation: employer's perception on high quality graduates - Awang Abd. Rahman @ Jusoh, Amilah; Abdul Rahim, Adibah; Ibrahim, Haslina (2012)
This paper reports on the expectation of employers towards university graduates. Being one of the stakeholders of the university, employers are the most relevant assessors to the graduates’ quality. The paper aims to report the following research objectives; to better understand issues and concerns from the employers towards graduates and the relevancy of the academic and non- academic programs on their professional career; and to highlight aspects of services needing attention for university improvement. The research employs qualitative method through in-depth interview. The interview sessions were held involving 10 employers based in Kuala Lumpur. They range from educational, financial, and public institutions, as well as corporate organizations. This paper found that academic achievement is still important but it should be accompanied with relevant knowledge and skills to ensure high quality of graduates as well as increasing the level of employability among them. By strengthening the link between university and employers, this research can enhance the university’s engagement in the sustainable development of the nation.